Pemeriksaan Pengujian Dan Penerapan Keselamatan Dan Kesehatan Kerja Pada Air Compressor Tank: Inspection, Testing, and Implementation of Occupational Safety and Health in Air Compressor Tanks - Pereira Maia Pinto, Gaspar (Blueprint Journal, 2025)
This study aims to analyze the methods of inspection, testing, and application of occupational safety and health (OHS) to pressure vessels in industry. occupational safety and health (OHS) on pressure vessels in industry. Inspection and testing are closely related to ensuring the structural integrity and operational safety of pressure vessels. Occupational safety and health is a primary focus to prevent workplace accidents and protect employees. Methods This research involved a survey of current inspection and testing inspection and testing practices, as well as analyzing data from incidents of work-related accidents and illnesses. incidents. In addition, the Air Compressor Tank Pressure Vessel Test Inspection was conducted at the PT X location is a periodic test check. Based on Minister of Manpower Regulation No. 37 Year 2016, the periodic test inspection stage consists of work activities, namely Document Inspection, Visual Inspection and NDT Testing. Documents, Visual Examination and NDT Testing, the results showed that Physical/Visual Inspection of the weld area found no weld defects, NDT (Non-Destructive Test) Inspection of the weld. NDT (Non-Destructive Test) Ultra sonic Wallthickness Testing on the plate was not found. found a difference in thickness (even thickness), Inspection of operating pressure in the weld area - Nozzle weld, valve no indication of leaking was found. Research This study concludes that the Safety valve and pressure gauge are checked internally and calibrated periodically. internal inspection and periodic calibration, operating pressure should not exceed the permitted pressure. operating pressure should not exceed the allowable pressure of 6 Bar, daily internal checks and maintenance are carried out periodically. periodically., Manual book and Hystory Manual book and Hystory card must always be maintained, when making repairs or replacing damaged components When repairing or replacing damaged components, it must be in accordance with the manufacturer's recommendations. on the Air Compressor Tank unit and document, the maintenance activities (Maintenance record must be done internally). maintenance activities (Maintenance records must be carried out internally periodically according to the manufacture), Comply with and implement all safety and health requirements. and occupational health. is fully responsible for the safe operation of the Air Compressor Tank Pressure Vessel.